2016
DOI: 10.1111/ejn.13281
|View full text |Cite
|
Sign up to set email alerts
|

Direct current stimulation of prefrontal cortex modulates error‐induced behavioral adjustments

Abstract: Commission of errors and conflict between choices might induce behavioral modulations through adjustments in the executive control of behavior and altered patterns of these modulations are detected in neuropsychiatric disorders. We examined the effects of transcranial Direct Current Stimulation (tDCS) applied over the dorsolateral prefrontal cortex (DLPFC) on error- and conflict-induced behavioral modulations. Two separate cohorts of participants performed two clinically relevant tests of executive control, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 70 publications
1
37
0
Order By: Relevance
“…reversal learning) but not others (i.e. task switching) are in line with some previous findings [9,10], but not entirely with others [14]. Methodological differences between studies including disparate measures of cognitive flexibility being used, on-line versus offline stimulation, left or right hemisphere targeting, size of the stimulating electrode, position of the reference electrode, the employment of between subjects versus crossover designs, duration of stimulation, means that comparisons should be made with caution.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…reversal learning) but not others (i.e. task switching) are in line with some previous findings [9,10], but not entirely with others [14]. Methodological differences between studies including disparate measures of cognitive flexibility being used, on-line versus offline stimulation, left or right hemisphere targeting, size of the stimulating electrode, position of the reference electrode, the employment of between subjects versus crossover designs, duration of stimulation, means that comparisons should be made with caution.…”
Section: Discussionsupporting
confidence: 92%
“…Cognitive flexibility has also been tested more directly using set-shifting/task switching tasks, but the results of these have not been entirely reproducible. Anodal tDCS to the dlPFC was shown to improve performance in three studies [11][12][13] and in a fourth study cathodal, but not anodal, stimulation improved certain aspects of cognitive flexibility (post-error slowing in the WCST) but not others (perseverative or total errors in the WCST) [14]. In two of the four studies cited [12,14], stimulation of left dLPFC was shown to be effective, whereas in the other two [11,13], the left and right hemisphere of the dlPFC contributed to different aspects of task-switching performance.…”
Section: Introductionmentioning
confidence: 95%
“…In previous studies, it was commonly observed that PES differed across participants (Steinborn et al, 2012). PES was found to be modulated by participant alertness and transcranial direct current stimulation intervention on the right dorsolateral prefrontal cortex (Mansouri et al, 2016;Wang et al, 2016). Thus, it is possible to improve post-error performance by experimental manipulation; however, whether WM training can improve post-error performance remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…HD-tDCS allows modulating cortical excitability and behavioral performance by administering an electrical current with superior spatial precision compared to conventional tDCS (Kuo et al, 2013;Villamar et al, 2013;Bortoletto et al, 2016). Please note, previous tDCS studies investigating effects of DLPFC stimulation on response inhibition and other forms of cognitive control (Vanderhasselt et al, 2013;Plewnia et al, 2015;Mansouri et al, 2016;Zmigrod et al, 2016) used "conventional" stimulation protocols, which do not allow to administer the current in a regionally specific way (Alam et al, 2016).…”
Section: Introductionmentioning
confidence: 99%